Ministerial Decree No. 259/2007 concerning the determination of the fees of listing the securities issues by the small and medium enterprises and the service charges for the transactions held therefore in the stock exchange : translated by The middle east library for economic services. As amended by decree No. 831/2014 - The middle east library for economic services, translator. (2025)
The Ministry of Investment Decree No, 259 of the Year 2007 Concerning the Determination of the Fees of listing the securities issued by the small and medium enterprises and the service charges for the Transactions held therefor in the Stock Exchange As Amended By Decree No. 831/2014 وزارة الاستثمار قرار رقم 259 لسنة 2007 بشأن تحديد قيد الأوراق المالية التى تصدرها الشركات الصغيرة والمتوسطة ومقابل الخدمات عن العمليات التى تتم لها بالبورصة معدل بالقرار 831 لسنة 2014